Luteolin promotes the sensitivity of cisplatin in ovarian cancer by decreasing PRPA1-medicated autophagy - Liu, Qing; Zhu, Dongchuan; Hao, Baozhen; Zhang, Zhiwei; Tian, Yongjie (Cellular and Molecular Biology, 2018)
Luteolin (LUT) is a flavone universally presented in plants. It shows an anti-carcinogenic effect in different cancers and could increase the sensitivity of cisplatin in colorectal cancer cell lines through Nrf2 pathway. However, the effect of luteolin on the sensitivity to ovarian cancer cells has not been studied. In this study, luteolin was found to suppress autophagy with reduced expression of LC3-II, but enhanced the inhibition of cell vitality and promoted apoptosis induced by cisplatin, leading to restoration of the sensitivity to cisplatin in ovarian cancer cells through CCK-8, flow cytometry and immunofluorescent assays. Although cisplatin elevated the PARP1 for cell survival, the cisplatin-induced expression of PARP1 was inhibited by luteolin a dose- and time- dependent manner through Q-PCR and WB assays. Further, PARP1 siRNA could further improve the LUT-induced inhibition of cell vitality and restore the sensitivity to cisplatin with reduced LC3-II levels. Our present work demonstrate that LUT can suppresses autophagy but enhance apoptosis induced by cisplatin and promote the sensitivity to cisplatin through suppressing the expression of RARP1 in ovarian cancer.